Measurement accuracy and uncertainty in plant biomechanics. (13th July 2019) - Nelson, Nathanael; Stubbs, Christopher J; Larson, Ryan; Cook, Douglas D
Abstract: All scientific measurements are affected to some degree by both systematic and random errors. The quantification of these errors supports correct interpretation of data, thus supporting scientific progress. Absence of information regarding reliability and accuracy can slow scientific progress, and can lead to a reproducibility crisis. Here we consider both measurement theory and plant biomechanics literature. Drawing from measurement theory literature, we review techniques for assessing both the accuracy and uncertainty of a measurement process. In our survey of plant biomechanics literature, we found that direct assessment of measurement accuracy and uncertainty is not yet common. The advantages and disadvantages of efforts to quantify measurement accuracy and uncertainty are discussed. We conclude with recommended best practices for improving the scientific rigor in plant biomechanics through attention to the issues of measurement accuracy and uncertainty. Abstract : Techniques to assess measurement accuracy and uncertainty provide numerous scientific benefits. This study provides a review and case studies of these techniques as applied to plant biomechanics.